2020
DOI: 10.1080/23311932.2020.1724385
|View full text |Cite
|
Sign up to set email alerts
|

Integrated application of compound NPS fertilizer and farmyard manure for economical production of irrigated potato (Solanum tuberosum L.) in highlands of Ethiopia

Abstract: Application of organic and inorganic fertilizers is essential for sustainable production of crops including potato. This study was therefore initiated to identify the optimum rate of farmyard manure (FYM) and blended compound NPS fertilizer for profitable production of potato in Koga Irrigation Scheme, Northwestern highlands of Ethiopia. Four rates of FYM (0, 4.5, 9, and 13.5 t ha −1) and NPS fertilizer (0, 81.7, 163.4, and 245.1 kg ha −1) were laid down in Randomized Complete Block Design with three replicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
5
7
0
Order By: Relevance
“…However, these yields were statistically at par with those of 5 t VC + 75% RDF, 7.5 t VC + 50% RDF, and 7.5 t VC + 25% RDF.The possible reason for the increased marketable tuber yield with higher VC and inorganic NP rates is that organic fertilizer sources' mineralization and mineral fertilizer through the growing periods do not expose the plants to nutrient stress, which results in the plants' nutrient stress maximum tuber yield. This result is also supported by several workers (Alemayehu et al, 2020;Gaur et al, 2017). Combined use of vermicompost and mineral NP showed a extremely significant difference (p<0.01) in the tuber dry weight.…”
Section: Total and Marketable Tuber Number Per Hillsupporting
confidence: 87%
See 1 more Smart Citation
“…However, these yields were statistically at par with those of 5 t VC + 75% RDF, 7.5 t VC + 50% RDF, and 7.5 t VC + 25% RDF.The possible reason for the increased marketable tuber yield with higher VC and inorganic NP rates is that organic fertilizer sources' mineralization and mineral fertilizer through the growing periods do not expose the plants to nutrient stress, which results in the plants' nutrient stress maximum tuber yield. This result is also supported by several workers (Alemayehu et al, 2020;Gaur et al, 2017). Combined use of vermicompost and mineral NP showed a extremely significant difference (p<0.01) in the tuber dry weight.…”
Section: Total and Marketable Tuber Number Per Hillsupporting
confidence: 87%
“…Consequently, nutrient supply integrated technique through chemical fertilizers in addition to organic manures is gaining significance, particularly for crops that are heavy feeders (Kumar et al, 2017). Furthermore, it has been observed that responsive and exhaustive yield such as potato's quality and quantity has been improved significantly under mineral and organic fertilizers' integrated use in comparison to the sole application of a recommended dose of applied nutrients as mineral (Alemayehu et al, 2020;Isreal et al, 2018). The environmental situation in this study area, i.e., the Masha district of southwestern highlands of Ethiopia, is part and parcel of the tropics.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors report increases in plant height and yield when the crop was fertilized with farmyard manure and NPS inorganic fertilizer, at a dose of 245.1 kg ha −1 [ 66 ]. In this sense, the presence of organic matter in the soil and its degradation by microorganisms allowed for adequate nutritional and moisture retention conditions, which is reflected in the height reached by the plants of treatments T7, T6 and T5.…”
Section: Resultsmentioning
confidence: 99%
“…The use of organic and mineral fertilizers can have a significant impact on potato yield. Phosphorus is one of the most restricted biomass elements present in less than one percent soluble in the soils of different regions depending on climate (Alemayehu et al 2020). Pelleting minituber with triple superphosphate increased the yield and yield components.…”
Section: Effect Of Minituber Pelleting On Yield and Yield Componentsmentioning
confidence: 99%